PENGEMBANGAN MODEL BISNIS BANK “X” DALAM MENDUKUNG INKLUSI KEUANGAN MENGGUNAKAN KERANGKA KERJA SOFT SYSTEM METHODOLOGY (SSM) - Wicaksono Sarwo Edi; Marimin .; Arief Daryanto; Imam Teguh Saptono (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
This research aims to develop a business model for Bank "X", which is a state-owned commercial bank, in supporting financial inclusion for micro and small segments. As a state-owned enterprise Bank “X” has a dual task, besides having to generate profits, it must also required to act as a agent of development. We still need to do more research to find out the most appropriate and effective business model for this area. The business model is mapped by utilizing 9 blocks of business model canvas developed by Osterwalder and Pigneur (2010). The study was conducted using the soft system methodology (SSM) framework according to Checkland (1981), which consists of seven stages. The seven SSM stages include: (1) finding a problem, (2) expressing a problem situation, (3) getting an essential definition, (4) making a conceptual model, (5) comparing it with the real world, (6) determining desirable - feasible change, and (7) suggestions for improvement. By carrying out these seven stages, an operational business model and sub-elements are produced which are the main keys or leverage points in operating a business model